REPORTS FOR MANAGEMENT. - Tiffany, K. C. (The Accounting Review, 1950)
Abstract As accountants, educators and executives, one is engaged almost continuously in the preparation of financial reports. One is convinced of the significance of financial reporting as a basis for intelligent executive action, and the importance of seeing that all reports contain the proper information and are designed to be of maximum use to the members of management who they are submitted. In this article the author reviews some of the principles and practices, which can be followed to render such reports as helpful and effective as possible. There are three levels of management to which financial reports must be made, top management, coordinating executives, and operating supervisors. The reports required by each vary in subject matter and in amount of detail, but the principles of reporting to each level are essentially the same. If the reports for top management should be comprehensive and concise, then so much the more should reports to operating supervisors be specific and concise, for the daily routines of production and selling demand that the supervisor be a man of action rather than an analyst.